2019
DOI: 10.1007/s11104-019-04176-w
|View full text |Cite
|
Sign up to set email alerts
|

Long term experimental drought alters community plant trait variation, not trait means, across three semiarid grasslands

Abstract: Background and Aims Grasslands are expected to experience droughts of unprecedented magnitude and duration in this century. Plant traits can be useful for understanding community and ecosystem responses to climate extremes. Few studies, however, have investigated the response of community-scale traits to extreme drought on broad spatial/temporal scales, with even less research on the relative contribution of species turnover vs. intraspecific trait variation to such responses.Methods We experimentally removed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 45 publications
1
41
0
Order By: Relevance
“…At the onset of each growing season (May–August) of each year, the rainout shelter roofs were installed and then removed at the end of the growing season (see Knapp et al., 2015; Luo, Zuo, et al., 2018 for further details on the rain‐out shelter). Each 6 × 6 m plot was hydrologically isolated by installing aluminium flashing to a depth of 1 m around the perimeter to reduce surface and subsurface water flow (Luo et al., 2019). The effects of rainout shelters on the light environment were small, permitting more than 90% penetration of photosynthetically active radiation (Luo et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the onset of each growing season (May–August) of each year, the rainout shelter roofs were installed and then removed at the end of the growing season (see Knapp et al., 2015; Luo, Zuo, et al., 2018 for further details on the rain‐out shelter). Each 6 × 6 m plot was hydrologically isolated by installing aluminium flashing to a depth of 1 m around the perimeter to reduce surface and subsurface water flow (Luo et al., 2019). The effects of rainout shelters on the light environment were small, permitting more than 90% penetration of photosynthetically active radiation (Luo et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Each 6 × 6 m plot was hydrologically isolated by installing aluminium flashing to a depth of 1 m around the perimeter to reduce surface and subsurface water flow (Luo et al., 2019). The effects of rainout shelters on the light environment were small, permitting more than 90% penetration of photosynthetically active radiation (Luo et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental drought changed biodiversity that can be explained by species turnover/re-ordering caused by the cumulative effect of extreme drought (Additional le 1 Table S1). Experimental drought can modify species either through shifts in genotypic abundance and phenotypic plasticity by acting as an environment lter [34,35]. On a temporal scale, there was no signi cant difference in species richness under extreme drought, which is contrary to other ndings that suggested that plant species richness is more sensitive to drought in the arid ecosystem [34,36].…”
Section: Discussionmentioning
confidence: 59%
“…Experimental drought can modify species either through shifts in genotypic abundance and phenotypic plasticity by acting as an environment lter [34,35]. On a temporal scale, there was no signi cant difference in species richness under extreme drought, which is contrary to other ndings that suggested that plant species richness is more sensitive to drought in the arid ecosystem [34,36]. One possible explanation for this difference could be the low soil moisture caused by extreme drought reduced the number of reproductive buds in more species [37,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation